Cardiac implantable electronic devices in tracheotomized muscular dystrophy patients: Safety and risks. (1st November 2016) - Fayssoil, Abdallah; Lazarus, Arnaud; Wahbi, Karim; Ogna, Adam; Nardi, Olivier; Lofaso, Frederic; Clair, Bernard; Orlikowski, David; Annane, Djillali
Abstract: Background/objectives: Muscular dystrophies are genetic muscle disorders, in which heart involvement and chronic respiratory impairment affect survival. Cardiac conduction disturbances require implantable cardiac pacemaker. Implantable defibrillators may also be necessary to prevent cardiac sudden death. The safety and risk of cardiac electronic devices' implantation are not known in patients with muscular dystrophy. We aimed to assess the risks related to cardiac implantable electronic devices (CIED) in muscular dystrophy patients ventilated by tracheostomy. Methods: We reviewed all medical charts of neuromuscular patients and identified all CIED implantations of pacemakers (PM) or defibrillators (ICD) in patients ventilated using tracheostomy. Results: Twelve device implantations were included, performed in 9 patients (5 DMD, 1 Becker muscular dystrophy and 3 DM1). Mean age was 39.9 years ± 13.0. All patients were wheel-chair bound and tracheotomized. Six pacemakers (PM) and 6 cardiac resynchronization (CRT) devices, including 2 defibrillators (CRT-D) were implanted. Following device implantation, two patients had a pneumothorax and one died from severe heart failure after an unsuccessful CRT implant attempt. Follow-up lasted up to 8 years (mean 2.6 ± 2.9 years), during which one patient presented a PM pocket infection, requiring PM explantation and epicardial reimplantation. Conclusion: We found a high prevalence of early complications (16.6% pneumothorax) after CIED implantation and an acceptable long-term infectious risk (8.3%). These results highlight the feasibility of CIED implantation in tracheotomized patients with muscular dystrophies and the need for a particular caution in the management of these patients during invasive procedures. ClinicalTrials.gov (identifier:NCT02501083 ).